FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Aries Jonathan; Irvan (E-Jurnal Akuntansi TSM, 2022)
Every company certainly wants to have great firm value for public to see. This study aims to examine and obtain empirical evidence about the impact of capital structure, profitability, firm size, sales growth, audit quality, gender diversity, and liquidity on firm value. Firm value is an indicator for investor to evaluate a company before they invest their fund. This study is using purposive sampling method which there are 71 manufacturing company that listed in Indonesia Stock Exchange and qualified with the criteria since 2018 until 2020, so there are 213 sample data that used in this study. Researcher examine independent variable on dependent variable using multiple regression model. This study use logarithm natural to measure firm size, audit quality is measured by dummy variable, gender diversity is measured by scale ratio and other variables are measured by financial ratio. The results of this study shows that capital structure and profitability have an impact on firm value, which means capital structure and profitability become the main indicators which affect the value of a company. While firm size, sales growth, audit quality, gender diversity, and liquidity have no impact on firm value